Stress and anxiety among nurses working in tertiary care hospitals in Nepal during COVID- 19 pandemic - Neupane, Mamata Sharma; Angadi, Siddeshwar; Joshi, Alisha; Neupane, Harish Chandra (Journal of Chitwan Medical College, 2020)
Background: Healthcare workers like nurses’ are the primary group who come in contact with patients, an important source of exposure to infected cases in healthcare settings. Corona Virus Disease 2019 (COVID-19) pandemic has brought all the health care professionals including nurses to work as a frontline member which may bring threat to mental wellbeing. The nurse’s psychological impact including stress and anxiety remains unknown. Hence, this study aimed to assess the stress and anxiety regarding COVID-19 among nurses working at Chitwan medical college and teaching hospital. Methods: A Descriptive cross-sectional survey was carried out among nurses working in Chitwan Medical College and teaching hospital. A total of 181 Nurses were selected through non probability consecutive sampling from various wards of Chitwan Medical College and Teaching Hospital. Data was collected using structured questionnaire. Data analysis was performed in SPSS version 20 for window using descriptive statistics. Results: The findings of the study revealed that out of 181 nurses 54.7% nurses reported moderate and 37.6% reported high level of stress and 10.5% of nurses reported mild to moderate level of anxiety. Conclusions: Considerable proportion of nurses working in different wards of hospital appear to experience some degrees of stress and anxiety during COVID-19 pandemic. Hence, it is essential that health organization takes measures to improve nurses’ mental health by intervening stress management programme to ensure positive attitude and maintain mental well-being.